Metformin-induced AMPK activation promotes cisplatin resistance through PINK1/Parkin dependent mitophagy in gastric cancer - Xiao, Yi-Yi; Xiao, Jin-Xing; Wang, Xiao-Yu; Wang, Tao; Qu, Xin-Hui; Jiang, Li-Ping; Tou, Fang-Fang; Chen, Zhi-Ping; Han, Xiao-Jian (Frontiers in Oncology, 2022)
Gastric cancer (GC) is one of the most common tumors worldwide, and cisplatin is a standard chemotherapeutic reagent for GC treatment. However, chemoresistance is an inherent challenge which limits its application and effectiveness in clinic. This study aims to investigate the mechanism of metformin-induced cisplatin resistance in GC. Intriguingly, the upregulation of mitophagy markers, mitochondrial fission, autophagy and mitophagosome were observed in SGC-7901/DDP cells compared to those in the SGC-7901 cells. Treatment with metformin significantly increased mitochondrial fission and mitophagy in both AGS and SGC-7901 cells, resulting in decreased ATP production, which unexpectedly protected GC cells against the cytotoxicity of cisplatin. In contrast, application of Chloroquine and 3-methyladenine, two inhibitors of autophagy, significantly alleviated the protective effect of metformin on SGC-7901 and AGS cells against cytotoxicity of cisplatin. Moreover, metformin also stimulated the phosphorylation of AMPK, and increased the expression of mitophagy markers including Parkin and PINK1 in the AMPK signaling-dependent manner. Consistently, the cell viability and cell apoptosis assay showed that metformin-induced cisplatin resistance was prevented by knockdown of AMPKα1. Taken together, all data in this study indicate that metformin induced AMPK activation and PINK1/Parkin dependent mitophagy, which may contribute to the progression of cisplatin resistance in GC.